Could truth stand without artifice? From the rhetorization of philosophy to the ontology of veridiction in Michel Foucault - Monge, Julia (Estudios de Filosofía, 2021)
This paper aims to analyze the alleged inversion of truth discourse ́s appraisal in Michel Foucault’s works between the early seventies and his last lectures of the eighties. We propose that, by reconstructing the contraposition between philosophical discourse and sophistical practice and the dispute between Socrates’s parrhesia and rhetoric presented in each moment, the question can be treated as the problem of truth discourse’s operation on the field of social practices. Considering the ethical and political stipulations and effects of both the rhetorical techné and the philosophical techné of discourse, we understand that between the “rhetorization of philosophy” and the “ontology of veridiction” that Foucault introduces in each occasion, there is not an inversion of perspective. Instead, there is a specification of the philosophical truth-telling as a practice that, confronted with other discourses indifferent to the truth, manifests a deep concern and commitment with a situated and relational construction of the ethos and the life in common.